Science Learning Model Based on Multisensory-Ecologi of Cognitive and Social Development in Early Chilhood - Helena, Helena; Yaswinda, Yaswinda; Tulum, La Mai; Rahmi, Azvi; Rahmalia, Denny; Intan, Nurul; Zeky, Serpuadi (International Journal of Islamic Studies Higher Education, 2024)
Science learning is important for early childhood so that they are able to understand the world and the environment around them, through various processes that are then recognized as scientific investigations. Children are expected to be able to solve the problems they face through science learning. This study aims to analyze the effectiveness of multisensory-ecology-based science learning models in improving cognitive and social development of early childhood. Social development in early childhood must also get a balanced portion. This research uses a 2x2 factorial experimental method. The sample consisted of early childhood divided into control and experimental groups. Data were collected through observation, cognitive tests, and social development scales. The results showed that children who learned using the multisensory-ecological learning model had significant improvements in cognitive and social aspects compared to the control group. Diverse sensory stimulation and active engagement in the learning environment contributed to better understanding of science concepts and more active social interaction. This learning model can be used as a reference for educators in designing more effective learning strategies for early childhood. It also supports inclusive education policies by considering the needs of diverse learners.